Disease Characteristics Profile and Preferred drugs Treatment Outcomes of JIA Subtypes: A Tertiary Care Hospital Experience in Bangladesh (Northern International Medical College Journal, 2025)
Background: Juvenile Idiopathic Arthritis (JIA) is a leading cause of chronic inflammatory joint disease in children. It has the potential to cause both short-term and long-term childhood morbidity and substantial disability which leave a long-lasting impact on the quality of life. Aim: To evaluate disease characteristics profile in children with Juvenile Idiopathic Arthritis (JIA) subtypes, effective medication and their outcome. Methods: This retrospective study was carried out using the medical records of follow-up center of the Rheumatology department of Bangladesh Shishu Hospital and Institute from January 2021 to December 2023.Ninety-five children who were diagnosed as JIA in this period were enrolled in this study. Data regarding clinical findings as articular, extra articular and systemic manifestations, biochemical profile, preferred drug, and remission or relapse rates of JIA subtypes were evaluated. Results: Among 95 cases 68 were male and 27 were female. Male : Female ratio being 2.5:1. Age range of the patients was 1 year to 15 years. Maximum number of patients presented beyond 5 years of age (67%). Duration of illness was less than 6 months in the majority (61%). In terms of disease characteristics, enthesitis related arthritis (ERA) were the most frequent (34.74%) followed by systemic JIA (29.47%). Arthritis was found in 100% of JIA patients. Knee and ankle were the most frequently affected joints accounting for 80% of the cases in both poly and oligoarticular subtypes. In this study, fever was found in 37.89% and morning stiffness in 36.84% cases. Rash was detected 64% in Systemic Juvenile Idiopathic Arthritis (sJIA) patients. In this study 10.52% of JIA had joint contractures and/or deformities. Uveitis, hepatomegaly and or splenomegaly, pericarditis were relatively infrequent. A life-threatening complication of sJIA, macrophage activation syndrome (MAS) was present in 14% cases. At initial presentation, overall 36.84% in JIA cases were anemic. Leukocytosis was in 52.63% and 33% cases had thrombocytosis. ESR and CRP were raised 34.73% and 56.84% respectively of JIA patients. Both ESR and CRP elevation were in sJIA. Rheumatoid factor positivity was 8.42% of overall JIA, half of patients were polyarticular. ANA was positive 38% in oligoarticular, 23% in polyarticular. HLA-B27 was positive 79% in ERA. The overall response rate to therapy was 45%. 27% had clinical remission on medication and 18% had remission off medication while 52% still had the active disease and 3% expired. Conclusion: The profile of JIA subtypes differ from each other. Used NSAID and steroids in the early period of disease was an effective treatment, especially addition of Methotrexate (MTX). Treatment with biologic agents in some of our patients flared after combination therapy with NSAID, steroids and MTX after 2 years became clinical remission.Northern International Medical College Journal Vol. 15 No. 1-2 July 2023-January 2024, Page 660-666